Synthesis and research of (Ni0.1Co0.3Mn0.6)3O4 as lithium‐ion battery conversion‐type anode using spent LiNi0.6Co0.2Mn0.2O2 batteries. (22nd March 2021) - Wu, Jie; Guo, Guanghui; Zhu, Jiaxin; Cheng, Yukun; Cheng, Xiangyu; Qiu, Jianghua
Summary: LiNi1‐x‐y Cox Mny O2 lithium‐ion battery, as the most installed battery of new energy vehicles, is facing the problem of large‐scale scrap. In this paper, (Ni0.1 Co0.3 Mn0.6 )3 O4 anode material with a microsphere structure was successfully synthesized by carbonate coprecipitation method, which was obtained by recycling spent LiNi0.6 Co0.2 Mn0.2 O2 lithium‐ion batteries through hydrometallurgy technology. This method eliminates the cumbersome separation steps, reduces the process cost, and realizes efficient recovery of valuable metals. The (Ni0.1 Co0.3 Mn0.6 )3 O4 anode material was characterized by inductively coupled plasma, X‐ray photoelectron spectroscopy, X‐ray diffraction analysis, scanning electron microscopy, and electrochemical measurements. The results show that (Ni0.1 Co0.3 Mn0.6 )3 O4 anode material has a microsphere structure with high crystallinity and exhibits a high discharge capacity (1575 mAh·g −1 at 100 mA·g −1 ) and a good cycling performance (659 mAh·g −1 at 100 mA·g −1 after 50 cycles). This work provides a new idea for the recycling of spent LiNi1‐x‐y Cox Mny O2 batteries. Abstract : In this paper, (Ni0.1 Co0.3 Mn0.6 )3 O4 anode material with a microsphere structure was successfully synthesized by carbonate co‐precipitation method, which was obtained by recycling spent LiNi0.6 Co0.2 Mn0.2 O2 lithium‐ion batteries through hydrometallurgy technology. The results show that (Ni0.1 Co0.3 Mn0.6 )3 O4 anode material has a microsphere structure with high crystallinity and exhibits a high discharge capacity (1575 mAh·g −1 at 100 mA·g −1 ) and a good cycling performance (659 mAh·g −1 at 100 mA·g −1 after 50 cycles).